Properties and Performance of Gas Diffusion Layer PEMFC Derived from Coconut Coir - Fredina Destyorini; Yuyun Irmawati; Henry Widodo; Deni Shidqi Khaerudini; Nanik Indayaningsih (Journal of Engineering and Technological Sciences, 2018)
In this work, carbon composite papers (CCP) were successfully produced by mixing 80 wt% carbon derived from coconut coir and 20 wt% binder (ethylene vinyl acetate and polyethylene glycol). The CCPs were prepared with two different forms of carbon material, i.e. powder (particle size: ± 74 µm) and fiber (length: ± 2 mm, diameter: 100-500 µm). Two types of papers were developed based on their composition. The first type, called CCP-1, was made from carbon in powder form (80 wt%), while the second one, CCP-2, was based on a combination of fiber (70 wt%) and powder (10 wt%). The influence of the carbon form on CCP properties were investigated, including electrical conductivity, porosity, hydrophobicity, microstructure, and its performance as a gas diffusion layer (GDL) in a stack of proton exchange membrane fuel cell (PEMFC) system. Based on the results, CCP-1 showed a slightly better fuel cell performance than CCP-2, which was also confirmed by its lower porosity, electrical conductivity, and water contact angle. The effect of carbon composite paper's properties, including its morphology and performance, are disscused in this paper in detail and compared with a commercially based GDL material (TGP-H-120).